How do types of interaction and phases of self-regulated learning set a stage for collaborative engagement?. (June 2016) - Järvelä, Sanna; Järvenoja, Hanna; Malmberg, Jonna; Isohätälä, Jaana; Sobocinski, Márta
Abstract: This study investigates how self-regulated learning phases are related to collaborative engagement in two different collaborative task conditions. It integrates SRL theory and the concept of engagement, including interaction in collaboration, as key characteristics of engagement. Forty-four second-year teacher education students worked in groups during a 7-week math didactic course. We collected 84 h of video recordings and coded the group's cognitive and socioemotional interaction and three phases of self-regulation within interaction, including forethought, performance and reflection. After that we analyzed the relationship between the interaction types representing collaborative engagement and SRL phases within two learning tasks. The results show that collaborative engagement did not differ between teacher-led and student-led tasks in terms of the interaction types. However, the results showed that the SRL phases occurred differently within cognitive and socioemotional interaction types when the two task conditions were compared. Findings concerning teacher-led tasks showed invariance in the occurrence of SRL phases across the task and highlighted the relationship between socioemotional interaction and the forethought phase. Additionally, findings concerning the student-led tasks showed systematic changes in the distribution of phases of SRL across sessions in all interaction types. Our results' theoretical and methodological implications for collaborative engagement research are discussed. Highlights: SRL and interaction types in collaboration are key characteristics of engagement. Video recordings of collaborative math tasks were collected. Task-focused interaction "sets a stage" for SRL and collaborative engagement (CE). CE did not differ in terms of interaction types, but in terms of the SRL cycle. Relationship between socio–emotional interaction and the forethought was highlighted.